1993
DOI: 10.1007/bf00376461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acclimatization to cold baths on men's responses to whole-body cooling in air

Abstract: The purpose of this study was to investigate the thermoregulatory mechanisms underlying artificial acclimatization to cold and to compare them with those of naturally acclimatized men. Six white men were cooled, nude, in air at 10 degrees C for 2 h before and after they had been acclimatized by ten daily cold (15 degrees C) baths of 30-60 min followed by rapid rewarming in hot (38-42 degrees C) water, and again 4 months later after acclimatization had decayed. Six control subjects also underwent the same tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Because of findings in rodent models and observations of increased energy expenditure in response to b3-adrenergic agonists (32) and different responses to cold in lean versus obese humans (33), it was speculated that decreased BAT mass and activity might be implicated in the development of obesity and type 2 diabetes (34). At that time it was, however, not possible to unequivocally prove the metabolic activity in human adults (35)(36)(37).…”
Section: (Re)discovery Of Bat In Human Adultsmentioning
confidence: 99%
“…Because of findings in rodent models and observations of increased energy expenditure in response to b3-adrenergic agonists (32) and different responses to cold in lean versus obese humans (33), it was speculated that decreased BAT mass and activity might be implicated in the development of obesity and type 2 diabetes (34). At that time it was, however, not possible to unequivocally prove the metabolic activity in human adults (35)(36)(37).…”
Section: (Re)discovery Of Bat In Human Adultsmentioning
confidence: 99%
“…In short-term cold acclimatization studies during which subjects were exposed to cold stimulation in an artificial climate chamber with a room temperature of 5 °C or were immersed in cold water, the heat insulation capacity was reportedly enhanced by a reduction in blood flow following acclimatization associated with a decrease in thermogenesis, a delay in shivering, and a decrease in distal skin temperature [13,14]. In contrast, no changes were seen in core body temperature and mean skin temperature from cold acclimation after cold exposure in a 5 °C room for 2 hours per day for 11 days [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to individual differences, this component may vary with the level of cold stimulation depending on factors such as exposure conditions and amount of clothing. Cold water immersion and other types of strong cold stimulation are often reported to result in a decrease in skin temperature and a decrease in thermogenesis [13,14], suggesting that the strength of the temperature environment may also affect the population in studies on seasonality because the strength of cold stimulation depends on their area of habitation.…”
Section: Introductionmentioning
confidence: 99%
“…A habituation of metabolic response to cold is the most common adaptation after repeated cold water immersion (Golden and Tipton 1988;Budd et al 1993;Jansky et al 1996a;Rees et al 2002). Since the participants in the previous studies were repeatedly immersed in colder water (10-15°C) than the present study, they decreased their deep body temperature more and increased metabolic heat production much more than in this study.…”
Section: Metabolic Responsementioning
confidence: 99%
“…In laboratory-based studies, habituation of the metabolic response to cold is the most common adaptation reported after repeated cold water immersions (Golden and Tipton 1988;Budd et al 1993;Jansky et al 1996a;Rees et al 2002). A relatively small number of studies have reported insulative adaptation after repeated cold immersions, including a significant decrease of skin temperature (Young et al 1986;Bittel 1987;Jansky et al 1996a, b) or increase in total peripheral resistance (O'Brien et al 2000) during cold exposure.…”
Section: Introductionmentioning
confidence: 99%